A retrospective study of the role of preoperative ultrasonography in the detection of deep vein thrombosis in 1750 patients with gastric and colorectal cancers. Issue 216 (August 2022) - Wang, Wei Dong; Wei, Jiang Peng; Gao, Rui Qi; Yang, Qin Chuan; Chen, Tong; Zhou, Hai Kun; Dong, Dan Hong; Yang, Xi Sheng; Yu, Peng Fei; Zhang, Ying; Li, Xiao Hua; Ji, Gang
Abstract: Background: There has been a lack of research in the past on the prevalence and risk factors associated with deep vein thrombosis (DVT) in patients with resectable gastric and colorectal cancers. The purpose of this study was to review the anatomical distribution, prevalence and risk factors associated with lower limb DVT in 1750 patients with preoperative gastric and colorectal cancers and to evaluate the role of preoperative ultrasonography in the detection of DVT in preventing postoperative pulmonary thromboembolism (PTE) in patients with gastric and colorectal cancers. Methods: A total of 1750 patients with gastric and colorectal cancers who underwent preoperative venous ultrasonography of the lower limbs were retrospectively reviewed. The risk factors associated with preoperative DVT were identified using univariate and multivariate logistic regression analysis. Results: Seventy-three of the 1750 patients with gastric and colorectal cancers had DVT detected by preoperative venous ultrasonography of the lower limb and the incidence of lower limb DVT was 4.17 % in 1750 patients with gastric and colorectal cancers. Univariate analysis showed a higher risk of DVT in patients who met the following criteria: aged ≥80 years, female sex, the performance status ≥1, stage IV, ASA class ≥ III/IV, and hypertension. Multivariate logistic regression analysis showed that female sex, stage IV and ASA class ≥ III/IV were significantly associated with DVT before gastric and colorectal cancer surgery. Conclusions: Our study showed that female sex, stage IV and ASA class ≥ III/IV were significantly associated with DVT before gastric and colorectal cancer surgery. Routine venous ultrasonography for the lower limb can identify the risk of PTE, which is of great significance in the prevention and occurrence of PTE.